Testosterone deficiency in the aging male. (February 2016) - McBride, J. Abram; Carson, Culley C.; Coward, Robert M.
Treatment for hypogonadism is on the rise, particularly in the aging population. Yet treatment in this population represents a unique challenge to clinicians. The physiology of normal aging is complex and often shares the same, often vague, symptoms of hypogonadism. In older men, a highly prevalent burden of comorbid medical conditions and polypharmacy complicates the differentiation of signs and symptoms of hypogonadism from those of normal aging, yet this differentiation is essential to the diagnosis of hypogonadism. Even in older patients with unequivocally symptomatic hypogonadism, the clinician must navigate the potential benefits and risks of treatment that are not clearly defined in older men. More recently, a greater awareness of the potential risks associated with treatment in older men, particularly in regard to cardiovascular risk and mortality, have been appreciated with recent changes in the US Food and Drug Administration recommendations for use of testosterone in aging men. The aim of this review is to provide a framework for the clinician evaluating testosterone deficiency in older men in order to identify correctly and treat clinically significant hypogonadism in this unique population while minimizing treatment-associated harm.